Concentration and crises: exploring the deep roots of vulnerability in the global industrial food system. Issue 1 (2nd January 2023) - Clapp, Jennifer
ABSTRACT: The world has experienced three global food crises in the past 50 years. While unique triggers sparked each of these crises, they all exposed extreme concentration within the global industrial food system at multiple scales – at the field, country, and global market levels. This multi-level concentration heightens vulnerability to worldwide food crises that have profound consequences for the world's most marginalized populations. With a focus on staple grains production and trade, this contribution traces the origins of the high degrees of multi-level concentration in the industrial food system and draws insights for debates on the current food systems transformation agenda.